Influence of Polymer Matrix on The Morphology and Crystallization Behavior of Electrospun Zinc Oxide Fibers - Aprilia, Annisa; Permana, Diki; Safriani, Lusi; Fitrilawati, Fitrilawati (Program Studi Fisika Universitas Negeri Jakarta, 2025)
ZnO finds widespread applications such as in photocatalysis, sensors, medicine, and other optoelectronic devices. The characteristics of ZnO can be influenced by several parameters, one of which is morphology. Fiber structures are attractive for research among various shapes and sizes due to their large effective surface area. ZnO fibers can be produced using electrospinning. However, the fiber morphology strongly depends on several important parameters, one of them is the characteristics of the polymer as a matrix. The molecular weight and concentration of the polymer and precursor material influence the solution viscosity, which is one of the crucial parameters in the electrospinning method. In this study, ZnO fibers were fabricated using three different polymers as matrices: PVP (polyvinyl pyrrolidone), PVAc (polyvinyl acetate), and PVA (polyvinyl alcohol). This research investigates the influence of polymer type on the morphology of ZnO fibers and crystallization behavior based on thermal characteristics. Based on SEM results, ZnO fibers were successfully fabricated with diameters ranging from 20–90 nm. The different characteristics are related to the type of polymer matrices and heating treatment. Only the PVA polymer could produce fibers before and after calcination, whereas the PVAc polymer-based fiber vanished after calcination. The disappearance of the fiber morphology is probably caused by the relatively high precursor (ZnAc) concentration, which leads to damage to the fibers formed during the calcination process. PVP failed to produce fibers, possibly due to its low polymer molecular weight, necessitating adjustment of other parameters. The removal of organic compounds through calcination continued until a temperature of 450ºC was reached. However, organic compounds were still identified in the samples based on FTIR characteristics. The ZnO/PVA fibers have hydrophobic surfaces, with the contact angle of water droplets being 117.75º. This characteristic is ideal for several applications such as antibacterial compounds or self-cleaning materials. Considering the inherent properties of ZnO, it can function as both an antibacterial and a photocatalytic agents simultaneously.